Production and characterisation of major allergens of local edible snails, Cerithidea obtusa and Pomacea canaliculata - Norazlin Salahudin Abd Aziz (Tanjong Malim, 2017)
Production and characterisation of major allergens of local edible snails, Cerithidea obtusa and Pomacea canaliculata by Norazlin Salahudin Abd Aziz